2009
DOI: 10.1590/s1677-04202009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Indian mustard (Brassica juncea L.) in response to salicylic acid under high-temperature stress

Abstract: Growth of Indian mustard (Brassica junceaLM salicylic acid (SA) at the 8-day stage and were sampled at 30 DAS. The plants exposed to temperature stress exhibited a significant (p < 0.05) decline in growth, and in levels of chlorophyll, nitrate reductase and carbonic anhydrase activities and photosynthetic parameters. A follow-up treatment with SA protected against the stress generated by temperature and significantly improved the above parameters. Antioxidative enzymes and levels of proline significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 37 publications
(20 reference statements)
2
20
0
Order By: Relevance
“…Among the genotypes stress tolerant index was higher in Co 99004 (0.84 and 0.86) and it range 0.70–0.84 and 0.71–0.86 at FP and GGP, respectively (Table 3). Hayat et al (2009) has also reported in mustard that NR activity decreased in heat stressed plants serves as a biochemical adaptation to conserve energy by stopping nitrate assimilation at the initial stage. Haba et al (2013) also recently stated that the activity of NR decreased in leaves exposed to high temperature in sunflower.…”
Section: Resultsmentioning
confidence: 99%
“…Among the genotypes stress tolerant index was higher in Co 99004 (0.84 and 0.86) and it range 0.70–0.84 and 0.71–0.86 at FP and GGP, respectively (Table 3). Hayat et al (2009) has also reported in mustard that NR activity decreased in heat stressed plants serves as a biochemical adaptation to conserve energy by stopping nitrate assimilation at the initial stage. Haba et al (2013) also recently stated that the activity of NR decreased in leaves exposed to high temperature in sunflower.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with those of Yildirim et al (2006), who showed that salinity caused a marked reduction in growth parameters of squash plants. One cause of growth rate reduction under stress conditions could be inadequate photosynthesis ( Figure 2D), less stomatal conductance ( Figure 2E), and consequently the limited carbon dioxide uptake (Hayat et al, 2009;Karlidag et al, 2011). Also, stress induced growth loss could be the result of inhibited cell division and expansion and increased H-pumping and apoplastic pH (Pitann et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al (2012) reported that the proline content increased in wheat under heat stress conditions [32]. The antioxidative activity and proline level of Indian mustard (Brassica juncea L.) decreased significantly in response to salicylic acid under heat stress, but the plants subjected to high temperatures showed a significant reduction in growth, photosynthesis traits and chlorophyll [24]. Jeshni et al (2014) showed that the proline content of chamomile increased in response to severe drought stress [8].…”
Section: Free Proline Concentrationmentioning
confidence: 99%